EFEKTIFITAS LATIHAN RANGE OF MOTION KOMBINASI JIGSAW PUZZLE TERHADAP KEKUATAN EKSTREMITAS ATAS PASIEN PASKA STROKE - Fransiska Anita Ekawati Rahayu Sa'pang; Felisima Ganut; Zabrina Queenita Mahesa Putri; Elania Anje; Felisita Yola; Getrudis Yusri (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Stroke is the leading cause of disability that causes upper limb hemiparesis, resulting in post-stroke patients having difficulty moving their hands, which impacts their ability to perform daily activities. If left untreated, this can lead to various complications such as contractures. During the rehabilitation phase, post-stroke patients need to undergo physical training, especially in the first 3 months after stroke, to pursue neuroplasticity so that hemiparesis can be restored. The purpose of this study was to analyze the effectiveness of combined ROM exercises and jigsaw puzzles in increasing upper limb muscle strength in post-stroke patients at a private hospital in Makassar. The research design used was a quasi-experimental pre-test and post-test equivalent control group design. The sampling technique used was purposive sampling. There were 40 respondents in each group. Data analysis used paired t-tests, with results showing that the combination of ROM exercises and jigsaw puzzles had an effect on the intervention group (p value < 0.05) with a mean value of 5.103, and that ROM exercises had an effect on the control group (p value < 0.05) with a mean value of 3.738. The results of the t-test showed a difference in upper extremity muscle strength between the intervention group and the control group (p value < 0.05). Thus, jigsaw puzzle combination ROM exercises are more effective at increasing muscle strength than regular ROM exercises, making them a suitable combination therapy for nursing care in hospitals.